Los reportajes de la prensa gallega, espejo de cuatro décadas de Historia - Parratt, Sonia (Historia y Comunicación Social, 2007)
This article summarises a research based on the thematic analysis of reportages published in the Galician press during four decades scarcely studied, as 1960-2000 are. Its main aim is to state the reflection of the main political, economical, social and cultural transformations as well as the evolution of Galician media industry in the topics chosen by the journalists for their reportages, a genre which goes deeper in the facts than everyday news. The study shows how the contents of the reportages have been adapting to the demands of a society that is permanently becoming more complex, mainly through thematic diversification and the increase of certain topics and the decrease of others.
Keywords: Thematic analysis; Reportage; History; Galicia